(untitled) (Experimental biology, 2015)
Indication of the lead acetate of the rats a dose 0,714 mg/kg was preformed of leukogram rats poisoned with lead acetate, 60th day decreased by 3 times compared 60 days. Common leukocyte indicators and indicators of the leukogram of the blood decreased by 3 times compared with the norm, reaching minimum volues. Immunosuppression was registered.